ANALYZE THE SPEED OF SIDE KICKS OF TEENAGE FIGHTERS - Hadidjah Harun; Syarif Hidayat; Hartono Hadjarati (Jambura Journal of Sports Coaching, 2020)
The purpose of the study was to analyze the speed of side kicks of teenage fighters at the Center for Student Training Education (PPLP) Gorontalo. This research method uses survey research in the form of a 15 second kick test, sit and reach test, standing board jump test. The sample of this study was conducted on 8 PPLP Gorontalo youth fighters. Based on the results of the study, the side kick speed of the Gorontalo PPLP adolescent fighter had a side kick speed performed within 15 seconds on average capable of doing as many as 28 for the right foot included in the excellent category and 26 for the left foot included in either category. In addition, the flexibility owned by Gorontalo PPLP adolescent fighters who were tested using sit and reach test was 45 cm which was included in the excellent category. Meanwhile, the power tested by standing board jump test power is 2.71 m which is included in the excellent category.